2013
DOI: 10.1073/pnas.1220635110
|View full text |Cite
|
Sign up to set email alerts
|

Candidate tumor suppressor BTG3 maintains genomic stability by promoting Lys63-linked ubiquitination and activation of the checkpoint kinase CHK1

Abstract: B-cell translocation gene 3 (BTG3) is a member of the antiproliferative BTG/ Transducer of ErbB2 gene family and is induced by genotoxic stress in a p53-and Checkpoint kinase 1 (CHK1)-dependent manner. Down-regulation of BTG3 has been observed in human cancers, suggesting that it plays an important role in tumor suppression, although the underlying mechanisms are unclear. Here, we report that BTG3 interacts with CHK1, a key effector kinase in the cell cycle checkpoint response, and regulates its phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…53 The tumor-suppressor BTG3 maintains genomic stability, and is downregulated in breast cancer, ovarian carcinoma and non-small-cell lung cancer. 29,[54][55][56] However, loss of BTG3 leads to acute cellular senescence in normal cells. 57 By interaction with cyclins, CDK6 activates the cell cycle at early G 1 .…”
Section: Discussionmentioning
confidence: 99%
“…53 The tumor-suppressor BTG3 maintains genomic stability, and is downregulated in breast cancer, ovarian carcinoma and non-small-cell lung cancer. 29,[54][55][56] However, loss of BTG3 leads to acute cellular senescence in normal cells. 57 By interaction with cyclins, CDK6 activates the cell cycle at early G 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Several reports demonstrate that BTG3 constitutes important negative regulatory mechanism for Src-mediated signaling and it inhibits transcription factor E2F1, suggesting it has a negative regulatory influence consistent with its role to inhibit progression into S-phase, meanwhile, BTG3 was identified as a transcriptional target of p53[14,18]. BTG3 interacts with CHK1, a key effector kinase in the cell cycle checkpoint response, and regulates its phosphorylation and activation[30]. Moreover, MiR-378 promotes cellular transformation, at least in part, by targeting and inhibiting TOB2, which is further elucidated as a candidate tumor suppressor to transcriptionally repress proto-oncogene cyclin D1[31].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrate that USP3 counteracts BTG3-promoted CHK1 K63-linked ubiquitination to regulate CHK1 chromatin association and activation in the maintenance of cell survival and genome stability. Previously, we had demonstrated that the CRL4 Cdt2 E3 ubiquitin ligase complex ubiquitinates CHK1 at the K132 residue, which promotes CHK1 chromatin association (11). As K132 is a critical residue at the kinase catalytic site (19), we postulated that the polyubiquitin chain linked to the residue may render CHK1 inactive by impeding substrate binding.…”
mentioning
confidence: 99%
“…Protein kinase B (AKT) phosphorylation of CHK1 preferentially retains the enzyme in the cytoplasm (10). Recently, we demonstrated that the B cell translocation gene 3 (BTG3) promotes CHK1 K63-linked ubiquitination by the ubiquitin E3 ligase CRL4 Cdt2 , which contributes to its nuclear localization, chromatin association, and activation to maintain cell survival and the mitotic checkpoint (11). Others have reported that, upon phosphorylation and activation, CHK1 is released from chromatin to phosphorylate its downstream targets (12).…”
mentioning
confidence: 99%